Foundations, Ideas and Resources for Prevention of cyberbullying - Hidalgo Lorente, Luis (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2025)
Cyberbullying is a reality and the digital world is not the problem. Education in prevention, so that Internet users behave in an appropriate and responsible way, is essential. Getting updated is almost a social obligation particularly in education. This paper presents foundations and resources to be applied at the school within the necessary adaptations.